The evolution of a coastal wedge in response to Plio-Pleistocene climate change: The Northern Adriatic case. (December 2020) - Amadori, Chiara; Ghielmi, Manlio; Mancin, Nicoletta; Toscani, Giovanni
Abstract: This work reconstructs the complex evolution of a coastal wedge in response to Pliocene tectonic activity and Pleistocene climate change recorded in the upper Neogene subsurface succession of the Friulian-Venetian Basin (FVB), since the latest Messinian sea-level drop event to the late Pleistocene. The FVB is the north-eastern portion of the wider Po Plain-Adriatic foreland basin (Northern Italy), which bounds to the east the whole Italian peninsula and is the place where most of the Italian hydrocarbon offshore fields presently occur. Also, the city of Venice and its surrounding lagoon is presently one of the sites most sensitive to land subsidence worldwide and even a few mm loss of ground elevations can significantly change the natural lagoon environments and threaten the city's survival. To this purpose, we have integrated seismics and well logs analysis with 1D-geohistory modelling on wells, using corrected paleobathymetric data, in order to extract decompacted sedimentation rates. The new age model is based on a complete chronostratigraphic revision of the continuously cored Venezia 1 well, correlated with other 12 hydrocarbon wells to form proper geological depth-calibrated profiles across the basin. Results suggest a major tectonic control on marine sedimentation and basin accommodation space changes during the entire Pliocene-early Pleistocene time, influenced by the Northern Apennines thrust fronts migration. On the contrary, the mid-upper Pleistocene deposition, characterized by a weak deformation, is mainly controlled by climate and basin geometry. During the early mid Pleistocene, an impressive progradational cycle (in the literature usually named "Sabbie di Asti group") followed the deposition of deep-water turbidites; in this work, we subdivide the different clastic bodies the formation is made of. The uppermost part of the "Sabbie di Asti group" is dominated by shallow-water to continental deposits showing a prominent regressive-transgressive cyclicity, where unfortunately chronological ties are limited. Nevertheless, 6 main cycles driven by 100 kyr Milankovitch-type ciclicity were laterally correlated by means of the well electric logs and linked to marine ∂ 18 O isotope and eustatic curves. Highlights: Evolution of the coastal wedge developed in the Apennine-Adriatic foreland setting. Depth-calibrated profiles across the Venetian-Adriatic basin. The Pleistocene deposition is mainly controlled by climate and basin geometry. The uppermost unit is made of 6 cycles driven by 100 kyr Milankovitch cyclicity.